PENGARUH LATIHAN SPEED, AGILITY DAN QUICKNESS (SAQ) TERHADAP KECEPATAN TENDANGAN DOLLYO CHAGI PADA ATLET TAEKWONDO PASAMAN BARAT - Nurul Aulya Rahma; Eri Barlian; Yogi Setiawan; Desi Purnama Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of Speed, Agility, and Quickness (SAQ) training on the Dollyo Chagi kick speed of West Pasaman Taekwondo athletes. SAQ training is a physical conditioning training method that focuses on improving movement speed, agility, and reaction time, which are essential in Taekwondo. This study used a quasi-experimental method with a One Group Pretest-Posttest Design. The study sample consisted of 20 West Pasaman Taekwondo athletes selected using a purposive sampling technique. The research instrument used a Dollyo Chagi kick speed test. Data analysis was performed using descriptive statistics, normality tests, homogeneity tests, and paired sample t-tests. The results showed an average pretest score of 28.9 and increased to 36.6 in the posttest. The results of the hypothesis test showed a significance value of 0.001 (<0.05). Thus, it can be concluded that Speed, Agility, and Quickness (SAQ) training has a significant effect on the Dollyo Chagi kick speed of West Pasaman Taekwondo athletes.